Hermeneutics of Translation – the Fundamental Aspect of Dialogue. Around the Concept of George Steiner - Włodarczyk, Rafał (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
George Steiner is one of the leading contemporary comparativists and philosophers of literature. One of the most important themes of his book from the 1970s, "After Babel: Aspects of Language and Translation", focus on the claim about the identity of understanding and translation, which in effect links dialogue to translation competence. In the article, referring to the thought and tradition of Judaism and Steiner’s original approach to understanding, I analyse and discuss the premises of his basic claim in relation to the phenomenon of dialogue, I study the consequences and draw conclusions from Steiner’s concept for the theory and practice of education.
Keywords: Steiner, George